Legal Certainty of Application of Electronic Archives in Keeping Minutes of Notary Deed as Authentic Evidence - Andi Muhammad Syuaib; Amin Purnawan; Akhmad Khisni (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to: to determine whether the application of the use of electronic archives for notarial deeds can provide legal certainty. The approach method in this research is normative law, the data source is obtained from literature and the legal materials used are primary, secondary and tertiary legal materials which are then analyzed by means of qualitative analysis. Based on the results of data analysis, it can be concluded thatthe use of electronic archives as a minimum of a notary deed has not yet obtained a strong legal basis, so it has not guaranteed legal certainty. Legal certainty can be achieved, if there are no conflicting provisions between one law and another. The legal substance in the use of electronic archives as a minimum of notary deeds has not been fully accommodated in the UUJN with the obligation to read the deed in the presence of witnesses and failure to fulfill this requirement will result in legal sanctions for the notary. The ITE Law, which is a legal basis for notaries, also does not provide an opportunity for electronic deeds by providing restrictions on notary deeds that are not included in electronic documents / information, so that they cannot be used as valid evidence. The incompatibility between UUJN and the ITE Law, and the ITE Law with the UUPT regarding the authority of notaries in the use of electronic records is clearly a separate obstacle for notaries. The current legal substance has not been able to facilitate the various interests of the community. Because the substance of the law has not accommodated the interests of the community, the existing legal regulations are not able to adapt to new things that are happening in the community, resulting in no guarantee of legal certainty. The substance of the law is not yet futuristic, because the regulation of the notary's authority cannot anticipate events that may arise in the future, namely the demands of the public so that notaries are able to make deeds electronically. The legal structure that was built has not been able to encourage the implementation of electronic services by notaries properly and optimally. In addition, the legal culture of the community tends to believe more in using conventional facilities than with technology.